2017
DOI: 10.3390/beverages3020026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Finings on the Perception of Beer

Abstract: Abstract:In recent years, a number of commentators have suggested that the use of finings to clarify beer can impair the flavour, because of the removal of key volatile aromatic molecules from the drink. However, are such claims necessarily correct? Unaware of any previous attempt to address this question empirically, we conducted both a blind and a sighted taste test. The test made use of two beers from the same batch, one made using finings and the other made without. In neither experiment did the use of fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Interestingly, two other studies (i.e., Reinoso-Carvalho et al, 2017 found no difference in the perceived bitterness of light and dark beers. In relation to a beer's clarity, Barnett et al (2017) reported that the addition of finings had no statistically significant effect on taste/flavour ratings, but people preferred the appearance of the beer that had been treated with finings. Lastly, there is some evidence to suggest that, universally, a moderate level of head and lacing has a significant, positive influence on certain expectations (e.g., a beer's expected quality and drinkability).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two other studies (i.e., Reinoso-Carvalho et al, 2017 found no difference in the perceived bitterness of light and dark beers. In relation to a beer's clarity, Barnett et al (2017) reported that the addition of finings had no statistically significant effect on taste/flavour ratings, but people preferred the appearance of the beer that had been treated with finings. Lastly, there is some evidence to suggest that, universally, a moderate level of head and lacing has a significant, positive influence on certain expectations (e.g., a beer's expected quality and drinkability).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study (i.e., Barnett, Juravle, & Spence, 2017) has been published assessing the influence of the clarity of a beer on taste/flavour perception. Barnett et al's study was conducted to assess the suggestion that using finings to clarify beer negatively impacts its flavour (see Moor Beer Company, 2017; Naylor, 2014; Protz, 2013).…”
Section: The Clarity Of the Beermentioning
confidence: 99%
“…Breaking down the color characteristics of a beer in more detail (e.g., by comparing differences in hue spectrum, or differences in haziness/cloudiness) could also help better disentangling the perceptual influence that a beer’s color can have on the tasting experience (cf. Barnett et al, 2017 ). Given recent work showing that the shape of glassware can influence the tasting experience as well (e.g., Spence et al, 2012 ; Spence and Piqueras-Fiszman, 2014 ; Spence, 2015a ; see Spence and Van Doorn, 2017 , for an overview), it is necessary to bear in mind that the color of a beer is never experienced in isolation, but is often affected by the glassware/material (e.g., plastic, glass) in which it is presented 11 .…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Breaking down the color characteristics of a beer in more detail (e.g., by comparing differences in hue spectrum, or differences in haziness/cloudiness) could also help better disentangling the perceptual influence that a beer's color can have on the tasting experience (cf. Barnett et al, 2017). Given recent work showing that the shape of glassware can influence the tasting experience as well (e.g., Spence et al, 2012;; see Spence and Van Doorn, 2017, for an overview), it is necessary to bear in mind that the color of a beer is never experienced in isolation, but is often affected by the glassware/material (e.g., plastic, glass) in which it is presented 11 .…”
Section: Discussion and Future Workmentioning
confidence: 99%